Untapped potential: Mobile device ownership and mobile payments in Canada - Marie-Hélène Felt; Angelika Welte; Katrina Talavera (Bank of Canada, 2024)
Mobile phones are ubiquitous around the world, making them obvious conduits for innovative payment technologies, or mobile payments. In Canada, five out of six adults regularly use a mobile phone. However, they have not started to use mobile payments at the same rate as other payment innovations, such as contactless card payments. In this paper, we present a twostage model of mobile phone and mobile payment use. An important feature of the model is that it controls for selectivity due to mobile device adoption. Controlling for selection into mobile phone usage reveals unobserved factors that have negative effects on mobile phone usage but a positive effect on the propensity to use mobile-type payments. These factors could be preferences or constraints. We present empirical evidence that providing people without a mobile phone access to payments with features similar to mobile payments could result in usage rates exceeding the current use among mobile phone owners. Therefore, people who are unable to acquire or choose not to own a mobile device might have unmet payment needs.
Keywords: C39; D12; E42; 330; Digital currencies and fintech; Econometric and statistical methods